The Evaluation of using Learning Videos for High School Mathematics Curriculum Subjects with Flipped Classroom Models on Learning Achievement in the IVET University Semarang - ., Nurmawati; ., Ismartoyo; kurniasih, Eem (KnE Social Sciences, 2024)
This research deals with the development of learning video media for high school mathematics curricula using the ADDIE stage model. This model, as the name implies, consists of five main phases or stages, namely (A) analysis, (D) design, (D) development, (I) implementation, and (E) evaluation. The implementation and evaluation phase was carried out in this second year, with an expanded test carried out in the mathematics education study program at IVET University Semarang in a fun and enjoyable way, with a posttest and a user response questionnaire with the following results: Based on research at IVET University Semarang, the results of the posttest were processed using The t-test obtained a result of 0% < 5%, then H0 was rejected. This means that we accept H1, which means that the results of learning mathematics with learning video media for high school mathematics curricula are better than conventional learning models, looking at the average learning achievement in the mean column, the group statistics table, it is obtained that the average of the experimental class was 85.50 while the average of the control class was 70.42. These results show that the learning outcomes of the experimental class were better than those of the control class. R Square value is 0.825 = 82.5%. This value means that the effect of virtual lab media on learning achievement is 82.5%. In comparison, 17.5% of learning achievement was influenced by other variables outside of the independent variables in this study. Keywords: the evaluation, learning videos, high school mathematics curriculum; flipped classroom models